2015
DOI: 10.1017/s0003055414000525
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Social Media’s Political Space: Estimating Ideology from Publicly Revealed Preferences on Facebook

Abstract: M any theories in political science rely on ideology at their core, whether they are explanations for individual behavior and preferences, governmental relations, or links between them. However, ideology has proven difficult to explicate and measure, in large part because it is impossible to directly observe: we can only examine indicators such as responses to survey questions, political donations, votes, and judicial decisions. One problem with this patchwork of indicator measures is the difficulty of studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
133
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(139 citation statements)
references
References 66 publications
(88 reference statements)
5
133
0
1
Order By: Relevance
“…Zafar et al (2016), have quantified the impartiality of social media posts by measuring how easy it is to guess the political leaning of its author. Bond and Messing (2015) inferred the political leanings of Facebook users by observing the endorsements of Facebook Pages of known politicians, while Wong et al (2016) measure the endorsements in terms of retweeting behavior of users to infer their political leanings. Cohen and Ruths (2013) used supervised methods to classify users into different groups of political activities and showed that it is hard to infer the political leaning of "normal" users.…”
Section: Measuring Political Bias On Social Media and The Webmentioning
confidence: 99%
See 1 more Smart Citation
“…Zafar et al (2016), have quantified the impartiality of social media posts by measuring how easy it is to guess the political leaning of its author. Bond and Messing (2015) inferred the political leanings of Facebook users by observing the endorsements of Facebook Pages of known politicians, while Wong et al (2016) measure the endorsements in terms of retweeting behavior of users to infer their political leanings. Cohen and Ruths (2013) used supervised methods to classify users into different groups of political activities and showed that it is hard to infer the political leaning of "normal" users.…”
Section: Measuring Political Bias On Social Media and The Webmentioning
confidence: 99%
“…Also, in Sect. 2, we have briefly described prior work which has developed techniques for measuring the bias of users (Purver and Karolina 2015;Makazhanov and Rafiei 2013;Fang et al 2015;Golbeck and Hansen 2011;Conover et al 2011a, b;Pennacchiotti and Popescu 2011;Bond and Messing 2015;Wong et al 2016) or content (Zafar et al 2016;Weber et al 2013) on social media as well as blogs and news stories (Adamic and Glance 2005;Yano et al 2010;Zhou et al 2011;Budak et al 2016;Munson et al 2013b) on the Web. In the future, when bias quantification schemes are developed for other search systems, for instance for videos (e.g., Youtube search) or music (e.g., Spotify), these methodologies can be plugged into our bias quantification framework and be used to analyze the bias of these other search systems.…”
Section: Generalizability Of Our Search Bias Quantification Frameworkmentioning
confidence: 99%
“…As long as users publish online information on their tastes and opinions, several scholars suggest that the analysis of social media allows to scale-on an ideological axis-the position of citizens and politicians. These studies adopt two different methodologies: some of them follow a network approach (Barberá, 2015;Bond and Messing, 2015;Ecker, 2015;Hanretty, 2011;King et al, 2011;Livne et al, 2011), while others focus on the content of social media posts (Boireau, 2014;Boutet et al, 2013;Conover et al, 2011;Livne et al, 2011;Sylwester and Purver, 2015).…”
Section: Estimating Policy Positions From Social Mediamentioning
confidence: 99%
“…Despite these findings, they defend their own method because of its computation speed, as it could be used for a real time estimation process. Bond and Messing (2015) use Facebook data to estimate ideology. They estimate the political inclination of more than 1,223 political pages on this social network and then use their estimates to produce an individual estimate for profiles that follow these pages.…”
Section: The Internet and Political Science Methodsmentioning
confidence: 99%